An efficient certificateless public auditing scheme in cloud storage. (18th July 2020) - Gao, Gaimei; Fei, Hongxia; Qin, Zefeng
Abstract: Cloud storage is a mode of online storage in which data are stored on multiple virtual servers usually hosted by third parties. Cloud service providers manage and operate data storage as services. The major concern in cloud storage is the integrity of outsourced data. Many public auditing schemes which authorize the third party auditor (TPA) to check the integrity of outsourced data have been proposed. However, most of them are based on traditional public key cryptosystems. This paper proposes an efficient certificateless public auditing Scheme (CL‐PAS) in cloud storage. In the process of challenge and auditing, CL‐PAS ensures that malicious cloud servers cannot forge auditing evidences to deceive TPA to pass the verification, and prevents curious TPA from recovering original data from auditing evidences. So it strengthens privacy preserving. Security analysis shows that CL‐PAS scheme meets the predetermined security requirements. The simulation and performance analysis results show that, compared with similar schemes, CL‐PAS scheme has the higher efficiency.